(untitled) (Journal on studies and research of academic knowledge, 2011)
The District Strategic Plan of Carmen del Parana, is the technical planning document that will guide the development of this town, the Plan is the product of a strategic planning work, conducted in 2010. The Strategic Development Plan of the district of Carmen del Paraná is directed under the stress of social actors intervention District and Region and the Government of Itapúa, Municipality, private entities, state agencies and organizations, drawn from the reality of Community Carmen del Paraná. The Plan seeks to turn the area into a territory stimulator and coordinator of sustainable socio-economic activities and synthesizes the right to gain a level and a decent standard of living for its population, which is a planned, sustained and consistent to allow reverse impacts generated in the territory. The Plan contains in its first part, a summary of the diagnosis of the district, followed by the second part of a summary of the participatory planning process, the third refers to the Proposed Strategic Plan, which defines the main lines or axes of development for the District of Carmen del Parana, made by social actors themselves and validated during the planning process. And Attachments, contains information regarding the work and results.